2020
DOI: 10.1177/0253717620962151
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Telepsychiatry: A United States Perspective with Relevance to India

Abstract: Telepsychiatry provides a platform for mental health care delivery in rural and remote areas. Hybrid Telepsychiatry model combines home-based telepsychiatry with domiciliary visits by community mental health workers. This involves use of different modes of teledevices which ensures safe and secure clinical platform. Research evidence supports that incorporating this model seems to use the specialist time efficiently where the resources are limited and services need to be catered for larger geographical communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Psychiatry supports collaborative models of care that promote multidisciplinary teams and the integration of digital technologies. Hybrid care uses both in-person and online methods to treat both individual patients and populations of patients [ 27 , 28 ]. Although technology-supported models are now the standard of psychiatric care, there is still a need to improve the provider experience [ 29 ] when using technology.…”
Section: Asynchronous Technologies In Clinical Carementioning
confidence: 99%
“…Psychiatry supports collaborative models of care that promote multidisciplinary teams and the integration of digital technologies. Hybrid care uses both in-person and online methods to treat both individual patients and populations of patients [ 27 , 28 ]. Although technology-supported models are now the standard of psychiatric care, there is still a need to improve the provider experience [ 29 ] when using technology.…”
Section: Asynchronous Technologies In Clinical Carementioning
confidence: 99%
“…It is dominated by telemedicine in health care (Rivest, Caron, & Desbeaumes Jodoin, 2021 ), e-learning in education (Alqahtani & Rajkhan, 2020 ) and teleworking in almost any kind of business (Zhang, Yu, & Marin, 2021 ). The absorption of telemedicine in the first year of the pandemic increased by 50% compared to the same period in the previous year (Koonin et al, 2020 ) and provided a variety of services from physical to mental health problems (Thippaiah, Harbishettar, Kumar, & Pandurangi, 2020 ; Watts et al, 2020 ). A meta-analysis showed that telemedicine is effective for some mental health interventions and reduce client waiting time compared to traditional therapy (Bennett, Ruggero, Sever, & Yanouri, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The primary health centres did not command the community's respect and trust due to the poor quality of services. Thus, it was found that creation of demand without appropriate improvement in services could lead to more harm than good [3,11,12,16,20,27,31,32,45,47,60,63,64,66,71,72,76,77].…”
Section: Risksmentioning
confidence: 99%